Increasing transplantability in Brazil: time to discuss Kidney Paired Donation - Bastos,Juliana (2021)
Abstract Introduction: Kidney transplantation (KT) is the best treatment for chronic kidney disease. In Brazil, there are currently more than 26 thousand patients on the waitlist. Kidney Paired Donation (KPD) offers an incompatible donor-recipient pair the possibility to exchange with another pair in the same situation, it is a strategy to raise the number of KT. Discussion: KPD ceased being merely an idea over 20 years ago. It currently accounts for 16.2% of living donors KT (LDKT) in the USA and 8% in Europe. The results are similar to other LDKT. It is a promising alternative especially for highly sensitized recipients, who tend to accumulate on the waitlist. KPD is not limited to developed countries, as excellent results were already published in India in 2014. In Guatemala, the first LDKT through KPD was performed in 2011. However, the practice remains limited to isolated cases in Latin America. Conclusion: KPD programs with different dimensions, acceptance rules and allocation criteria are being developed and expanded worldwide to meet the demands of patients. The rise in transplantability brought about by KPD mostly meets the needs of highly sensitized patients. The Brazilian transplant program is mature enough to accept the challenge of starting its KPD program, intended primarily to benefit patients who have a low probability of receiving a transplant from a deceased donor.